PENGEMBANGAN MEDIA PEMBELAJARAN KARTU DISKUSI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATA PELAJARAN IPAS DI KELAS V SD - Dwi Hijriani; Yeni Erita (STKIP Pesisir Selatan, 2026)
Objective: This study aims to develop discussion cards that are valid, practical, and effective in enhancing elementary school students’ critical thinking skills, particularly in the social studies component of the Integrated Social and Natural Sciences (IPAS) curriculum, using the topic “My Rich and Diverse Indonesia.” Method: This study employed the Research and Development (R&D) method using the ADDIE model. It involved fifth-grade students at SDN 03 Lubuk Begalung as test subjects, as well as students at SDN 10 and SDN 22 Lubuk Begalung for broader implementation. Data were collected through validation sheets, practicality questionnaires, and pretest-posttest assessments, then analyzed descriptively and using the N-Gain formula. Results: The validity test conducted by experts yielded a score of 89.66% (highly valid). The practicality of the media fell into the “practical” to “highly practical” categories, as indicated by the responses of teachers (94%–96%) and students (79.53%–86%). The effectiveness of the media recorded an N-Gain of 0.1998 (low) during the pilot test and 0.3117–0.4333 (moderate) in the schools where it was implemented. Novelty: This study presents an innovative interactive discussion card medium specifically designed for the integrated IPAS (Science, Technology, Engineering, and Mathematics) component of the Merdeka Curriculum, which has rarely been researched to foster students’ critical thinking through collaborative learning.